Assessing Greek small and medium‐sized enterprises’ flood resilience capacity : index development and application - Antonis Skouloudis and Walter Leal Filho and Panagiotis Vouros and Konstantinos Evangelinos and Ioannis Nikolaou and Georgios Deligiannakis and Thomas Tsalis (Journal of flood risk management, 2022)
Floods signify one of the most common, widespread and destructive natural perils, affecting approximately 250 million people and causing billions in losses on an annual basis. Such high impact – low probability environmental perturbations can cause abrupt changes and disruption to business entities in flood-prone areas in terms of asset damages, operational interruptions and increased costs which result in loss of capital and labour, declining revenue and growth. It is therefore critical for businesses to identify such risks and, ultimately, to effectively build their resilience to such physical challenges. Small and medium-sized enterprises (SMEs) in particular are more ill-prepared to face flooding compared to large companies. Understanding the ability of SMEs to become more resilient to floods is crucial as they account for 99% of all enterprises, constitute the major employer and contributor of the total value-added of the private sector. In this study, a composite index of factors linked to the resilience capacity of SMEs to flooding is proposed and tested. A sample of Greek SMEs located in three flood-prone areas (n = 391) was administered a structured questionnaire pertaining to cognitive, managerial and contextual factors that affect the ability to prepare, withstand and recover from flooding events. Through the proposed index, a bottom-up, self-assessment, approach is set forth that could assist in standardising such assessments with an overarching aim of reducing the vulnerability of SMEs to floods. This is achieved by examining critical internal and external parameters affecting SMEs' resilience capacity which is particularly important taking into account the limited resources these enterprises tend to have at their disposal and that they can generate single points of failure in dense supply chain networks.
Keywords: floods; Greece; index development; organisational resilience capacity; small and medium-sized enterprises